Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s1751731109003838
|View full text |Cite
|
Sign up to set email alerts
|

Differences in productive robustness in rabbits selected for reproductive longevity or litter size

Abstract: The aim of this work was to evaluate the ability of a line selected for reproductive longevity (LP) to confront productive challenges compared to a line selected during 31 generations for litter size at weaning (V). A total of 133 reproductive rabbit does were used (72 and 61 from LP and V lines, respectively). Within each line, three groups with different levels of productive effort were planned: PP9, inseminated at day 4 after the first partum and with nine kits during the second partum, and inseminated afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 38 publications
(36 reference statements)
9
38
2
1
Order By: Relevance
“…Moreover, the NDFd was higher (1.4%; P<0.05) for LP than for V36 animals (+1.8%, P<0.05). As observed by Pascual et al (2008) and Theilgaard et al (2009), females from LP line showed a higher feed intake (19.21 g DM/d) during lactation period than the V line. However, the difference between V16 and V36 (-14.0 g DM/d) was not statistically significant.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the NDFd was higher (1.4%; P<0.05) for LP than for V36 animals (+1.8%, P<0.05). As observed by Pascual et al (2008) and Theilgaard et al (2009), females from LP line showed a higher feed intake (19.21 g DM/d) during lactation period than the V line. However, the difference between V16 and V36 (-14.0 g DM/d) was not statistically significant.…”
Section: Resultssupporting
confidence: 62%
“…high temperatures and feed restriction). They delayed reproductive senescence (Theilgaard et al, 2007) and improved their lifespan (Theilgaard et al, 2006;Sanchez et al, 2008), resulting in more robust animals (Theilgaard et al, 2009). All of these findings could be related to a better use of the energy resources available to cope with the reproduction effort, as hypothesised by Pascual et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Line V, in contrast, seemed to adjust the DE intake and milk yield to ensure a higher PFT at weaning. The effort of V does to accrete more PFT than LP does was also observed by Theilgaard et al (2009), but cannot be clearly elucidated from Theilgaard et al (2007). However, Theilgaard et al (2007) observed a tendency of V WP is the weaning to partum interval.…”
Section: Genetic Differences In Nc Environmentmentioning
confidence: 81%
“…A likely reason for this difference between studies is the difference in the reproductive rhythm adopted in each one. When the reproductive rhythm was less intense (insemination at 25 or 30 dpp), the initial live weight differences between lines were maintained (Theilgaard et al, 2007 and, whereas when it was more intense (insemination at 4 or 11 dpp) the live weight differences disappeared (Theilgaard et al, 2009). …”
Section: Genetic Differences In Nc Environmentmentioning
confidence: 99%
See 1 more Smart Citation